Strategies to Develop Institutional Linkages with other Organisations - Kulkarni, D. S.; Dandoti, S. Z. (Journal of Engineering Education Transformations, 1996)
In the context of the economic and industrial development of our country, the role played by engineers and engineering activities is extremely critical. In our economy, 35% of our industrial investment belong to engineering industries. The output from these engineering industries account for 33% of our total industrial output.